Peran guru dalam pembelajaran - Uqbah, Sa’diyatul (Maliki Interdisciplinary Journal, 2024)
This article discusses the importance of the role of teachers in education in elementary schools, which not only teaches academic materials, but also shapes students’ character and morals. Teachers serve as mentors who help students prepare for academic and social challenges. A holistic education integrates cognitive and affective aspects. Therefore, the role of teachers in creating a learning environment that supports and encourages the development of social, moral, and academic skills is very important in forming a competent and characterful generation.